Role of Local Government in Women Political Participation: A Case Study of Punjab (2001-2008) - Ilahi, Waqar; Khan, Ehtaisham Ahmed; Din, Muhammad Shahab Ud (Annals of Human and Social Sciences, 2023)
The study evaluates the role of the local government in fostering women’s political engagement by evaluating government initiatives during 2001-2008 time-period. The province of Punjab experienced notable changes in local governance after Pervez Musharraf assumed power in 1999 and implemented measures for devolution of power to the local governance structure. The methodology of the study is based on qualitative analysis of government documents, non-governmental organization reports and academic articles to uncover the relationship between women empowerment and local governance initiatives in Punjab. The findings of the research illustrate the differential implications of local government endeavors on the political participation of women in Punjab. While certain initiatives have succeeded with Punjab reflecting the highest percentage of women participation in local governance. But issues persist that necessitates legislative changes, civic education and capacity building programs to eliminate impediments to fair participation of women in politics.